The influence of smart tourism applications on perceived Destinations image in Kelantan - Nurul Najihah Ramli; Nurul Natasha Che Wan Sarif; Nurul Natasha Mohd Maliki; Nurul Natasya Mat Hassan (2022)
This study is about the influence of smart tourism applications on perceived destination image in Kelantan. A smart tourism application gives the effect on a tourist's behavioral intention. However, this is often an issue among tourists who are new to being a smart tourist. Therefore, this study was conducted to examine the relationship between smart information systems and perceived destination image. In addition, this study was conducted to determine the relationship between smart sightseeing and perceived destination image. Other than that, this study was conducted to identify the relationship between e-commerce systems and perceived destination image. Finally, this study was conducted to identify the relationship between smart forecasting and perceived destination image. The quantitative method used was a questionnaire. About 384 respondents were selected among tourists Gen Z to answer questions to find out the influence of smart tourism applications on perceived destinations' image. The final results of this study indicate that there is a significant relationship between smart information systems, smart sightseeing, e-commerce systems and smart forecasting with the influence of smart tourism applications. In four independent variables, smart information systems and e commerce systems are positively affected in information search and smart sightseeing and smart forecasting positively affected for e-recommendations.